2017
DOI: 10.1021/acssynbio.7b00174
|View full text |Cite
|
Sign up to set email alerts
|

Managing the SOS Response for Enhanced CRISPR-Cas-Based Recombineering in E. coli through Transient Inhibition of Host RecA Activity

Abstract: Phage-derived "recombineering" methods are utilized for bacterial genome editing. Recombineering results in a heterogeneous population of modified and unmodified chromosomes, and therefore selection methods, such as CRISPR-Cas9, are required to select for edited clones. Cells can evade CRISPR-Cas-induced cell death through recA-mediated induction of the SOS response. The SOS response increases RecA dependent repair as well as mutation rates through induction of the umuDC error prone polymerase. As a result, CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 58 publications
1
76
0
1
Order By: Relevance
“…Meanwhile, as expected, knockout of recA significantly increased the lethality of DSBs in the bacterial chromosome as induced by the CRISPR/Cas9 system (Figure 3a), consistent with the conclusions of previous reports(18, 23). Even though it has been suggested that genome editing can benefit from the blocking of recA expression (18, 39), we argue that via the rational selection of sgRNAs (Figure 3b, Table S9) the FPR of genome editing can be significantly reduced without the tradeoff of genome instability derived from blocking the inherent DNA repairing pathways in bacteria.…”
Section: Resultsmentioning
confidence: 64%
“…Meanwhile, as expected, knockout of recA significantly increased the lethality of DSBs in the bacterial chromosome as induced by the CRISPR/Cas9 system (Figure 3a), consistent with the conclusions of previous reports(18, 23). Even though it has been suggested that genome editing can benefit from the blocking of recA expression (18, 39), we argue that via the rational selection of sgRNAs (Figure 3b, Table S9) the FPR of genome editing can be significantly reduced without the tradeoff of genome instability derived from blocking the inherent DNA repairing pathways in bacteria.…”
Section: Resultsmentioning
confidence: 64%
“…The genes deoB and thyA and corresponding mutants deoB p.309Stop and thyA 755-762del were cloned into a modified pTRC plasmid in which the laqI and promoter region were replaced by the tetR repressor gene and promotor region derived from plasmid Plasmid pEM-Cas9HF1-recA56 (addgene Addgene plasmid # 89962 (Moreb et al, 2017) M9 minimal media + folAmix, then washed with fresh M9 media without folAmix and plated at different concentration of folAmix. Growth rate values are the mean ± SD of at least 3 biological replicates.…”
Section: Effect Of Deob and Thya Expressionmentioning
confidence: 99%
“…Additionally, numerous studies have demonstrated the Cas9 activity is not only dependent on a specific gRNA sequence but also on the genomic context (host organism, cell type, etc.). 16,17 The same gRNAs can have highly variable activity between animal models, cell lines, and even strains of E. coli . [16][17][18] In this study, we confirm that "non-target" sites, representing a significant level of context dependent variability, competitively bind to Cas9/gRNA complexes, and can significantly impact on-target activity of Cas9/gRNA complexes in vivo .…”
Section: Introductionmentioning
confidence: 99%